Study of the Dependence of Ignition Temperature on the Outer Cone Angle of a Fuel Injector - Singh, Subhkaran (Journal of Graphic Era University, 2024)
Internal combustion engines are still a hot topic in research as there is still vast room for improvement. Compression ignition engine research is occurring very rapidly, new diesel blends are being experimented with every day, and duel fuel and tri-fuel diesel engines are becoming a norm. Most of the credit for this research goes to the computation modeling and rapid development of new numerical schemes. This research is one such attempt to capture the spray combustion, using n-heptane as a fuel, with OpenFOAM CFD code. The particles of heptane fuel are injected into the combustion chamber, where the combustion process occurs. The heat transfer between the spray combustion and the surrounding air is realized using the Ranz-Marshall heat transfer model, the mass transfer from the droplets to the surrounding gas due to evaporation and boiling is modeled using the evaporation and boiling model. A conical injector is used for the spray of the fuel and ignition temperature at 20∘/40∘/60∘/ 80∘/100∘ thetaOuter is recorded and the results are presented in the form of a graph, showing how 60∘ is an optimum angle where the ignition temperature is low(not the lowest) and maximum temperature achieved is the highest. This research would be very useful in finding the cone angle of a spray using the various values of thetaOuter, as just by changing the angle of the spray an adverse effect on ignition temperature and maximum temperature is observed. This would allow better ignition temperatures without even changing any other properties of the compression ignition engine. The mesh used is coarse to speed up the calculations, the recorded data shows a change in temperature with various angles, and a bird’s eye view of the flame propagation is also discussed as the change in angle profoundly affects the flame shape.